Verbal Learning Style as the Least Preferred Learning Style of Students in an Asian Country - Samuel S. Poliden (JPAIR Institutional Research Journal)
Learners develop a preferred way of choosing their learning styles because of their genetic makeup, their particular life experiences, and the demands of their present environment. Hence, the study aimed to determine the learning styles of freshmen students in the language class at Benguet State University, Philippines. Using descriptive - survey method, a questionnaire was used to gather data. It also used the Felder-Solomon Index of Learning Styles (FILS) which consisted of 44 questions designed to identify learning styles of learners. The study showed that their dominant learning style is Visual while Verbal is the least. According to their degree programs, the dominant learning style of the Bachelor in Secondary Education and Doctor of Veterinary Medicine students is Sensory while Bachelor of Science in Nursing, Bachelor of Science in Home Economics, Bachelor of Science in Information Technology, Bachelor of Science in Agricultural Engineering, and Bachelor of Science in Agriculture are all inclined to Visual. Based on the empirical findings and conclusions of the study, the researcher recommends that teachers should devise classroom activities suited for the students' learning styles focusing more on their verbal learning style that will activate their communication skills.